(untitled) (Bangladesh Journal of Pharmacology, 2013)
Our study investigated the effects of antisense oligodeoxynucleotide targeting survivin on human gastric cancer cells. Human gastric cancer cells were incubated with antisense oligodeoxynucleotide targeting survivin for pre-designed durations, and then the cell growth was observed under light and electronic microscopes. Electrophoresis of fractured DNA fragments was performed to detect the DNA distribution and telomere repeat amplification protocol (TRAP) was used for the detection of telomerase activity. Antisense oligodeoxynucleotide targeting survivin could induce the apoptosis of human gastric cancer cells which were characterized by plasma membrane blistering, chromatin condensation, nuclear fragmentation, and formation of apoptotic bodies. Electrophoresis showed characteristic DNA ladder. Flow cytometry revealed hypo-diploid apoptosis peak before G1 phase and the telomerase activity was significantly inhibited. These results demonstrated antisense oligodeoxynucleotide targeting survivin can induce the apoptosis of gastric cancer cells to inhibit their proliferation.